Miniaturization Potential of Additive-Manufactured 3D Mechatronic Integrated Device Components Produced by Stereolithography - Niklas Piechulek; Lei Xu; Jan Fröhlich; Patrick Bründl; Jörg Franke (Micromachines)
Three-dimensional Mechatronic Integrated Devices (3D-MIDs) combine mechanical and electrical functions, enabling significant component miniaturization and enhanced functionality. However, their application in high-temperature environments remains limited due to material challenges. Existing research highlights the thermal stability of ceramic substrates; yet, their reliability under high-stress and complex mechanical loading conditions remains a challenge. In this study, 3D-MID components were fabricated using stereolithography (SLA) 3D-printing technology, and the feasibility of circuit miniaturization on high-temperature-resistant resin substrates was explored. Additionally, the influence of laser parameters on resistance values was analyzed using the Response Surface Methodology (RSM). The results demonstrate that SLA 3D-printing achieves substrates with low surface roughness, enabling the precise formation of fine features. Electric circuits are successfully formed on substrates printed with resin mixed with Laser Direct Structuring (LDS) additives, following laser structuring and metallization processes, with a minimum conductor spacing of 150 µm. Furthermore, through the integration of through-holes (vias) and the use of smaller package chips, such as Ball Grid Array (BGA) and Quad Flat No-lead (QFN), the circuits achieve further miniaturization and establish reliable electrical connections via soldering. Taken together, our results demonstrate that thermoset plastics serve as substrates for 3D-MID components, broadening the application scope of 3D-MID technology and providing a framework for circuit miniaturization on SLA-printed substrates.